Pengaruh Kemiskinan dan Pengangguran Terhadap Indeks Pembangunan Manusia (IPM) Indonesia 2018-2022 - Adim, Abd (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
Poverty and unemployment are important indicators for achieving the success of a Country’s development. This study aims to test the influence of poverty and unemployment on the Human Development Index (HDI) in Indonesia. The resecarch population consisted of 35 provinces in the study using secondary data from the central statistics Agency of Indonesia and the province of Indonesia in the periode 2018-2022. Data analysis is done using fixed effect model (FEM), with eviews sofware program. The results of this study show that, poverty first has a positive and significant effect on the human development index in Indonesia. In this study wanted to test multocolinearity test and autucorrelation test. In hepotesis test want to know test (partila-t) menyeluruheous (f-test), and coefficient of determination (R2)